Preparation of cerium (III) carbonate dispersion
By using a composition of polymer and cerium (III) carbonate particles in the exterior paint, the problems of tone retention loss and undesired color formation are solved, and better color retention and gloss retention are achieved.
Patent Information
- Application Number
- CN202180022258.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-20
- Filing Date
- 2021-02-09
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-02-09
AI Technical Summary
In the field of exterior paint, the prior art is difficult to effectively prevent the degradation of colorants caused by mediating photocatalytic polymers and TiO2, resulting in loss of tone retention and undesirable color formation.
By using a composition containing polymer and cerium (III) carbonate particles, fading in the coating is reduced and the formation of undesired color bodies is prevented. The nanoscale dispersion of cerium (III) carbonate particles is stable in water and is used to prepare aqueous dispersions and combine with polymers to enhance the protection effect.
Significantly reduces fading and undesired color formation in the paint, improves tone retention and gloss retention, and extends the fresh appearance life of the coating.
Smart Images

Figure BDA0003851780830000051
Abstract
Description
[0001] Citations of Related Applications
[0002] This application claims priority to U.S. Provisional Application No. 62 / 992,424, filed on March 20, 2020. Background Art
[0003] In the field of exterior paints, it is desirable to have a paint-coated substrate that maintains a fresh appearance over an extended period of time. This "freshly painted" appearance can be measured by three interrelated properties: dirt-pickup resistance (DPUR), gloss retention, and tintretention. Of these, tintretention is particularly important as darker and deeper colors become more popular in exterior applications.
[0004] The loss of hue retention, also known as fading, is believed to be caused by photocatalytic polymer-mediated and colorant degradation caused by TiO2, which is used as an opaque pigment in most paint formulations. TiO2 particles absorb UV light and, in the presence of water, generate highly reactive hydroxyl groups that reactively degrade the polymer backbone and colorant, causing gloss loss, fading, and undesirable color formation.
[0005] The attempt to mitigate the degradation of external coatings has been largely achieved by using UV absorbers to prevent free radical formation and antioxidants to quench free radicals by blocking UV light before polymer or colorant degradation occurs. Unfortunately, UV absorbers require sufficiently long path lengths to absorb and are therefore only effective in transparent top coatings. Antioxidants (such as hindered amines, hindered phenols, carbon center free radicals (radicals), phosphites and sulfides) tend to leach from the coated substrate, thus only providing short-term protection. Therefore, it would be advantageous to find more effective ways to achieve color retention and reduce undesirable color formation in the coated surface in the field of external coatings. Summary of the invention
[0006] The present invention addresses the need in the art by providing a composition comprising a polymer and cerium (III) carbonate particles. DETAILED DESCRIPTION
[0007] In a first aspect, the invention is a composition comprising a polymer and cerium (III) carbonate particles. The composition of the invention can be used to reduce discoloration and reduce the formation of unwanted color bodies in coatings.
[0008] In this aspect, the polymer preferably forms a solution or dispersion with the liquid. In one embodiment of this aspect of the invention, the composition is an aqueous dispersion of polymer particles (latex) and cerium (III) carbonate particles. The particle size of the cerium (III) carbonate particles is not limited, but for some applications (such as semi-gloss coating formulations), it is preferred that the cerium (III) particles are nano-sized particles.
[0009] As used herein, "nanoscale cerium (III) carbonate particles" refers to cerium (III) carbonate particles having a z-average particle size of no more than 500 nm as measured by dynamic light scattering. The term "nanodispersion" refers to an aqueous dispersion of nanoscale cerium (III) carbonate particles. In another aspect, the nanoscale cerium (III) carbonate particles have a z-average particle size of no more than 300 nm; in another aspect, no more than 200 nm; in another aspect, no less than 50 nm.
[0010] The nano-scale dispersion of cerium (III) carbonate is advantageously prepared as follows: a water-soluble cerium (III) ammonium salt, a water-soluble carbonate, and a capping ligand are advantageously mixed together in water at a pH in the range of 8 (preferably 9) to 12 (preferably 11) under conditions sufficient to produce a nano-dispersion of cerium (III) carbonate particles. The mole: mole ratio of the water-soluble cerium (III) ammonium salt to the water-soluble carbonate is preferably in the range of 2: 1, more preferably 1: 1 to preferably 1: 20, more preferably 1: 10; the mole: mole ratio of the water-soluble cerium (III) ammonium salt to the capping ligand is preferably in the range of 50: 1, more preferably 30: 1 to 1: 1. The reaction is typically carried out at or near ambient temperature, and the reaction is typically completed within one hour.
[0011] As used herein, "water-soluble cerium (III) ammonium salt" refers to a cerium (III) ammonium salt that is at least 10% soluble in water in the proportion used. A preferred water-soluble cerium (III) ammonium salt is cerium (III) ammonium nitrate. Similarly, the term "water-soluble carbonate" refers to an alkali metal or ammonium carbonate or bicarbonate that is at least 10% soluble in water in the proportion used. Examples of water-soluble carbonates include sodium carbonate, potassium carbonate, ammonium carbonate, sodium bicarbonate and potassium bicarbonate, with ammonium carbonate being preferred.
[0012] As used herein, a "capping ligand" is an amine carboxylic acid or salt thereof, an amine phosphonic acid or salt thereof, or a polymer functionalized with a carboxylic acid group or salt thereof. "Amine carboxylic acid" refers to a compound comprising at least one amine group and at least one carboxylic acid group. Preferably, the amine carboxylic acid is aminoacetic acid or a salt thereof; preferably, aminoacetic acid comprises at least two carboxylic acid groups; more preferably, aminoacetic acid is diacetamide, triacetamide, or tetraacetamide, examples of which include ethylenediaminetetraacetic acid (EDTA), ethylenediaminediacetic acid (EDDA), and nitrolotriacetic acid (NTA).
[0013] The polymer functionalized with carboxylic acid groups can be, for example, a homopolymer resulting from the homopolymerization of carboxylic acid-containing monomers such as acrylic acid, or a copolymer resulting from the copolymerization of carboxylic acid-containing monomers with one or more additional monomers (which do not require carboxylic acid functionalization). An example of a homopolymer functionalized with carboxylic acid groups is polyacrylic acid (PAA).
[0014] "Amine phosphonic acid" refers to a compound comprising at least one amine group and at least one phosphonic acid group. The end-capping ligand may include one or more phosphonic acids and one or more carboxylic acid groups, and salts thereof. Examples of amine phosphonic acids include aminotrimethylphosphonic acid (ATMP), 6-amino-2-[bis(carboxymethyl)amino]hexanoic acid, and N-(phosphonomethyl)iminodiacetic acid (PIDA).
[0015] In another aspect, the present invention is a composition comprising an aqueous dispersion of cerium (III) carbonate particles having a z-average particle size in the range of 5 nm to 500 nm. The dispersion preferably also comprises a capping ligand, which is believed to promote the formation of nano-dispersed particles while stabilizing the particles to prevent aggregation.
[0016] Based on the weight of water and cerium (III) carbonate, the concentration of cerium (III) carbonate in water is preferably in the range of 0.2 wt %, more preferably 0.5 wt %, most preferably 1 wt % to 25 wt %, more preferably 21 wt %. More typically, the concentration of the reactants is adjusted to form a final dispersion of 1 to 5 wt % solids; compositions with higher solids content can be prepared by centrifugation, followed by removal of the supernatant or vacuum removal of water.
[0017] Based on the weight of polymer, the weight ratio of polymer to cerium carbonate (III) is preferably 0.2 wt %, more preferably 0.5 wt %, and most preferably in the range of 1 wt % to 10 wt %, more preferably 8 wt %, and most preferably 5 wt %. Compositions comprising latex and cerium carbonate (III) particles are useful in the field of coating compositions, especially coating compositions comprising pigments or colorants or both. Pigments include opaque pigments and extenders. Opaque pigments include TiO , BaSO and organic hollow sphere polymer particles (HSP). TiO can be anatase or rutile, and is passivated or unpassivated. The commercial example of TiO is Ti-Pure-R706 TiO and DeGussa P25 TiO photocatalyst. Compositions can include combinations of anatase and rutile, passivated and unpassivated TiO .
[0018] Suitable extenders include carbonates, silicon dioxide, silicates, aluminosilicates, phosphates, and non-hollow organic microspheres. More specific examples of extenders include talc, clay, mica, sericite, CaCO3, nepheline, feldspar, wollastonite, kaolinite, dicalcium phosphate, and diatomaceous earth.
[0019] The colorant may be organic or inorganic, dispersible (tint) or soluble (dyes). Examples of suitable colorants include methylene blue, phthalocyanine blue, phthalocyanine green, monoarylide yellow, diarylide yellow, benzimidazolone yellow, heterocyclic yellow, DNA orange, pyrrole orange, quinacridone magenta, quinacridone violet, dioxazine violet, quinacridone red, naphthol red, pyrrole red, metallized azo red, nonmetallized azo red, carbon black, lampblack, black iron oxide, yellow iron oxide, brown iron oxide, and red iron oxide.
[0020] In another aspect, the invention is a composition comprising a polymer or copolymer such as poly(methyl methacrylate) (PMMA) dissolved in a solvent such as chloroform in the presence of dispersed cerium (III) carbonate particles. The composition of this aspect of the invention can be used, for example, in the housing of an automotive headlight.
[0021] In another aspect, the present invention is a composition comprising cerium (III) carbonate particles and a neat polymer. This composition can be prepared by mixing cerium (III) carbonate particles with an extruded polymer melt.
[0022] The composition may contain other components such as rheology modifiers, surfactants and dispersants.
[0023] Examples of suitable polymers include polyacrylates, poly(styrene-acrylates), polystyrene, polyvinyl acetate, polyurethanes, poly(vinyl acetate-acrylates), silicones, epoxies, polyolefins, cellulose, and polysilicates. Examples of preferred latexes include the following structural units: a) methyl methacrylate or styrene; b) an acrylate monomer which is n-butyl acrylate, ethyl acrylate, or 2-ethylhexyl acrylate; c) a carboxylic acid monomer which is methacrylic acid or acrylic acid. It may also be desirable to functionalize the latex with a phosphoric acid monomer such as phosphoethyl methacrylate.
[0024] As used herein, the term "structural unit" of a named monomer refers to the remaining portion of the monomer after polymerization. For example, the structural unit of methyl methacrylate is shown below:
[0025]
[0026] The structural unit of methyl methacrylate
[0027] The dashed lines represent the points of attachment of the building blocks to the polymer backbone.
[0028] Cerium (III) carbonate nanodispersions are particularly useful in applications such as latex paint formulations where color and gloss retention are desirable.
[0029] Example 1-4 - Preparation of aqueous nanodispersion of cerium (III) carbonate particles
[0030] In the following examples, the z-average particle size was determined by dynamic light scattering.
[0031] Example 1 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by EDTA
[0032] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. EDTA (50 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 seconds while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0033] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water (including 5 min vortex mixing) to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0034] To study the effect of EDTA loading on the properties of cerium (III) carbonate, the example was repeated twice using 100 mg and 500 mg of EDTA. The z-average particle size of the cerium carbonate particles was found to be 125 nm (50 mg EDTA), 118 nm (100 mg EDTA), and 114 nm (500 mg EDTA).
[0035] Example 2 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by NTA
[0036] The procedure described in Example 1 was essentially followed, except that NTA (65 mg) was used instead of EDTA as the capping ligand. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0037] This example was repeated using 32.5 mg of NTA. The z-average particle sizes of the cerium carbonate particles were found to be 157 nm (32.5 mg NTA) and 115 nm (65 mg NTA).
[0038] Example 3 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by PIDA
[0039] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. PIDA (72 mg) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 seconds while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0040] The product mixture is divided into four 40mL centrifuge tubes and then centrifuged for 6min at 20,000rpm. The white product in each tube is collected and washed with 25mL water (including 5min vortex mixing) to ensure that soluble nitrates and excess ammonium carbonate are removed. The final product after washing and centrifugation is obtained as a wet paste with 20wt% solid content. The z-average particle size of the cerium carbonate particles is found to be 105nm.
[0041] Example 4 - Preparation of an aqueous dispersion of nanosized cerium (III) carbonate particles stabilized by PAA
[0042] An aqueous solution of cerium (III) ammonium nitrate tetrahydrate (2 g in 100 mL of deionized water) was added to a 250 mL plastic bottle. PAA (500 mg of a 50% aqueous solution, MW = 2000 g / mol) and ammonium carbonate (1 g) were dissolved in water (50 mL) and then added to the solution of cerium (III) ammonium nitrate tetrahydrate within 25 s while stirring (600 rpm) for 10 min. The pH of the mixture was observed to be 8.0 ± 0.3.
[0043] The product mixture was divided into four 40 mL centrifuge tubes and then centrifuged at 20,000 rpm for 6 min. The white product in each tube was collected and washed with 25 mL of water (including 5 min vortex mixing) to ensure removal of soluble nitrates and excess ammonium carbonate. The final product after washing and centrifugation was obtained as a wet paste with a solid content of 20 wt%.
[0044] The example was repeated twice using 1.1 g and 2.2 g of 50% aqueous PAA.The z-average particle size of the cerium carbonate particles determined by dynamic light scattering (DLS) was found to be 105 nm (0.5 g PAA), 105 nm (1.1 g PAA), and 20 nm (2.2 g NTA).
[0045] Example 5-7 - Preparation of coating formulations using dyes and hues
[0046] In the following preparation, the acrylic adhesive had the following characteristics: (49BA / 50MMA / 1MAA), z-average particle size = 98nm, solids content 40.2 wt.%.
[0047] Preparation of paint formulations using dyes:
[0048] Two separate dispersions were prepared as follows:
[0049] A. Ti-Pure-R706 TiO2 (3.5 g), optionally 10% DeGussa P25 TiO2 photocatalyst based on the weight of Ti-Pure-R706 TiO2, TAMOL TM 1124 dispersant (trademark of Dow Chemical Company or its affiliates, 0.3 wt. % relative to the weight of the pigment), 1 M NH4OH (10 μL) and 3.5×10 -4Aqueous solution of M Congo red dye or methylene blue dye (0.7 mL) was mixed at 1700 rpm in the presence of ZrO beads (10 mm) to form a TiO slurry. The ZrO beads were removed from the slurry and then additional amounts of dye solution (1.27 mL) were added to the slurry over time. The mixture was then mixed (3500 rpm for 3 min) to obtain 4.65 g of a 75 wt.% pigment slurry.
[0050] B. Combine 2 wt.% to 5 wt.% solids of cerium (III) carbonate (relative to the weight of Ti-Pure-R706 in step A) (20% solids wet paste prepared as described above without or with a capping ligand, as described in Example 2) with water (0.86 mL to 0.44 mL, depending on the solids). The pH of the resulting solution was adjusted to pH 9 with 1 M NH4OH. The mixture was sheared (3500 rpm for 4 min) and then sonicated (10 min).
[0051] The slurry from step A was mixed with acrylic binder (12.79 g) under stirring. The dispersion from step B was mixed with the slurry from step A and the mixture was sheared (3500 rpm for 1 min). ACRYSOL TM 2020E thickener (a trademark of The Dow Chemical Company or its affiliates, 0.6 g) was added to the mixture and mixed (3500 rpm for 3 min) to obtain a final paint formulation at about 16% pigment volume concentration (PVC).
[0052] Preparation of paint formulations using colorants:
[0053] Combine Ti-Pure-R706 TiO2 (4.6g), TAMOL TM 1124 dispersant (0.3 wt.% relative to the weight of the pigment), 1M NH4OH (10 μL), DeGussa P25 TiO2 photocatalyst (0.36 g), Colortrend Organic Red 808 colorant (0.44 g) and water (1.53 g) were mixed at 2100 rpm in the presence of ZrO2 beads. The ZrO2 beads were removed from the slurry and the slurry was mixed again (3500 rpm, 3 min) to obtain 7 g of 75 wt.% pigment slurry. The slurry was mixed with the dispersion described in step B (except that only cerium (III) carbonate was prepared according to Example 2) to form a final paint formulation with a PVC of about 16%.
[0054] UV-induced photodegradation of coatings
[0055] The paint formulation was applied on a polyacrylic acid substrate using a 3 mil bar applicator. The applied coating was dried under ambient conditions for 72 h. The dried coating was then irradiated under 254-nm UV light (140-150 Lux) for 4 h.
[0056] A portion of the coating (200 mg) was scraped off the polyacrylic acid substrate, combined with 1 mL of ethanol, and sonicated for 15 min. The mixture was then vortexed for 5 min, and the supernatant containing the residual dye was analyzed by UV-vis spectroscopy to determine the extent of dye degradation.
[0057] Example 5 - Dye degradation by UV-Vis, containing P25
[0058] As described above, when a sample containing Ti-R706-TiO2, DeGussa P25, acrylic binder, Congo red dye and cerium (III) carbonate without a capping ligand was exposed to UV light, the degree of dye degradation was 8%. In contrast, the degree of degradation without cerium (III) carbonate was 40%.
[0059] Example 6 - Dye degradation by UV-Vis without P25
[0060] As described above, when a sample containing Ti-R706-TiO2, acrylic binder, methylene blue dye and cerium (III) carbonate without a capping ligand was exposed to UV light, the degree of dye degradation was 0%. In contrast, the degree of degradation without cerium (III) carbonate was 15%.
[0061] Example 7 - Toner Degradation by UV-Vis, Containing P25
[0062] As described above, when a sample containing Ti-R706-TiO2, DeGussa P25, an acrylic binder, an organic red toner, and cerium (III) carbonate with a capping ligand (as described in Example 2) was exposed to UV light, it was found that color retention was completely retained. In contrast, the sample without cerium (III) carbonate showed significant color loss.
[0063] UV-induced photodegradation of polymethyl methacrylate:
[0064] A mixture of a) PMMA dissolved in CHCl3 and b) cerium (III) carbonate particles (prepared as in Example 1 or 3; 2 or 5 wt.% based on the weight of PMMA) was poured into a watch glass and allowed to dry for 16 h under ambient conditions. After drying for 16 h, the PMMA film was then irradiated for 4 h under 254-nm UV light (140-150 Lux).
[0065] Example 8 - UV Photodegradation of PMMA with EDTA-capped Cerium(III) Carbonate
[0066] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate capped with EDTA (2 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.
[0067] Example 9 - UV Photodegradation of PMMA with PIDA-terminated Cerium(III) Carbonate
[0068] No yellowing was observed for the irradiated PMMA film containing cerium (III) carbonate end-capped with PIDA (5 wt % based on the weight of PMMA). In contrast, the cast film without cerium (III) carbonate exhibited significant yellowing.
[0069] These studies demonstrate that cerium(III) carbonate substantially improves discoloration in coatings produced from the coating formulations and significantly reduces undesirable color formation.
Claims
1. A composition comprising a polymer and cerium (III) carbonate particles, wherein the cerium (III) carbonate particles are nanoscale particles having a z-average particle size of 5-500 nm, and wherein the composition further comprises a capping ligand, wherein the capping ligand is an amine carboxylic acid or a salt thereof; wherein the composition is used to maintain color and gloss in a coating and to avoid the formation of undesirable colors.
2. The composition according to claim 1, wherein The polymer forms a solution or dispersion with the liquid. 3 . The composition according to claim 2 , which is an aqueous dispersion of polymer particles and the cerium (III) carbonate particles.
4. The composition according to claim 2, wherein The polymer forms a solution in an organic solvent, and wherein the polymer is a polymer or copolymer of methyl methacrylate.
5. The composition according to claim 3, wherein The polymer particles are polyacrylates, poly(styrene-acrylates), polystyrenes, polyvinyl acetates, polyurethanes, poly(vinyl acetate-acrylates), silicones, epoxies, polyolefins, celluloses and polysilicates.
6. The composition according to claim 5, further comprising a colorant.
7. The composition according to claim 5, further comprising a pigment.
8. The composition according to claim 7, wherein The pigment is selected from the group consisting of TiO2, BaSO4, organic hollow spherical polymer particles, talc, clay, mica, sericite, CaCO3, nepheline, feldspar, wollastonite, kaolinite, dicalcium phosphate, diatomaceous earth, and non-hollow organic microspheres.
9. A composition comprising a polymer and cerium (III) carbonate particles, wherein: The cerium (III) carbonate particles are nano-sized particles, and wherein the composition further comprises a capping ligand, and the capping ligand is an amine carboxylic acid or a salt thereof.
10. The composition according to claim 9, wherein The composition is an aqueous dispersion of polymer particles and the cerium (III) carbonate particles, the composition further comprising a pigment, the pigment comprising TiO2, wherein the TiO2 is anatase, rutile, or a combination thereof; and wherein the TiO2 is passivated, unpassivated, or a combination thereof.
11. The composition according to claim 10, wherein The polymer particles include the following structural units: a) methyl methacrylate, styrene or a combination thereof; b) an acrylate monomer, wherein the acrylate monomer is n-butyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate or a combination thereof; and c) a carboxylic acid monomer, wherein the carboxylic acid monomer is methacrylic acid, acrylic acid or a combination thereof.
12. The composition according to claim 10, wherein The polymer particles include structural units of methyl methacrylate, n-butyl acrylate and methacrylic acid.
13. The composition according to claim 12, wherein The polymer particles further comprise structural units of phosphoethyl methacrylate.
Citation Information
Patent Citations
Coloring material dispersion liquid for color filter, color resin composition for color filter, color material, color filter, liquid crystal display apparatus, and light emitting display apparatus
CN107111023A
Novel water-based drier and preparation method thereof
CN109321027A
Cathodic electrodeposition coating material composition
JP2002294175A
Method for preparing cerium carbonate and cerium oxide
US20110244237A1
Color material dispersion liquid for color filter, color resin composition for color filter, color material, color filter, liquid crystal display device, and light-emitting display device
US20170342271A1